2022
DOI: 10.1002/aoc.6722
|View full text |Cite
|
Sign up to set email alerts
|

Topical progress in medicinal applications of self‐assembled organoplatinum complexes using diverse Pt(II)‐ and N‐based tectons

Abstract: The last decade witnessed a flourishing advancement in the design and synthesis of discrete Pt‐based metallamacrocycles self‐assembled using coordination bonds. Such supramolecular entities were obtained using novel nitrogen‐based ligands and have wide and versatile applications such as chemical sensors, catalysts, theranostic agents, optical materials, drug delivery, and others. Herein, we present a concise review of recently reported metallacycles obtained using various N‐functionalized donor and Pt acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Coordination-based spherical assemblies (CBSAs) have recently gained attention in the medicinal context. [41][42][43][44] CBSAs are well-defined nanosized materials that are constructed by coordination of multi-topic ligands to transition metals. [45][46][47][48] 53 Whereas some studies have suggested the application of CBSAs as genotoxic agents, to the best of our knowledge their potential as gene delivery agents has never been investigated.…”
Section: The Bigger Picturementioning
confidence: 99%
“…Coordination-based spherical assemblies (CBSAs) have recently gained attention in the medicinal context. [41][42][43][44] CBSAs are well-defined nanosized materials that are constructed by coordination of multi-topic ligands to transition metals. [45][46][47][48] 53 Whereas some studies have suggested the application of CBSAs as genotoxic agents, to the best of our knowledge their potential as gene delivery agents has never been investigated.…”
Section: The Bigger Picturementioning
confidence: 99%